2006
DOI: 10.1038/sj.ejhg.5201585
|View full text |Cite
|
Sign up to set email alerts
|

A text-mining analysis of the human phenome

Abstract: A number of large-scale efforts are underway to define the relationships between genes and proteins in various species. But, few attempts have been made to systematically classify all such relationships at the phenotype level. Also, it is unknown whether such a phenotype map would carry biologically meaningful information. We have used text mining to classify over 5000 human phenotypes contained in the Online Mendelian Inheritance in Man database. We find that similarity between phenotypes reflects biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
516
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(528 citation statements)
references
References 36 publications
6
516
0
6
Order By: Relevance
“…The phenotypic similarities were downloaded from the literature [37], including pairwise similarities for 5,080 disease. The similarity is ranged from 0 to 1, where a larger value means higher phenotypic similar between a disease pair and vice versa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic similarities were downloaded from the literature [37], including pairwise similarities for 5,080 disease. The similarity is ranged from 0 to 1, where a larger value means higher phenotypic similar between a disease pair and vice versa.…”
Section: Methodsmentioning
confidence: 99%
“…To filter the small similarities that mean low confidences among disease pairs, we introduce a parameter to remove the edges that similarities are less than Îą=0.1, the mean of all disease similarities. Existing studies have shown that relationships between diseases have noises [37], and thus a noise filtering process is helpful in improving the performance of detecting disease genes [33]. Finally, we obtain a heterogeneous network including 15,078 nodes and to 5,782,818 edges.…”
Section: Methodsmentioning
confidence: 99%
“…The first group of methods uses some notion of similarity between drugs (e.g., chemical similarity [149], similarity between gene expressions induced by drug actions [74], or drug-side effect similarity [150]) to group drugs and infer a novel drug candidate for repurposing from the group that can perform the same action as other drugs in the group. The second group of methods uses similarities between diseases (e.g., phenotype similarity [151], or similarity between disease symptoms [152]) to group diseases and to infer a novel drug for repurposing by expanding known associations between the drug and some members of the group to the rest of the group. Other approaches use target-based similarities [153], i.e., protein sequence similarity [154], or 3D structural similarity [155], to infer novel drugs.…”
Section: Computational Methods For Drug Repurposing and Personalised mentioning
confidence: 99%
“…While genetics and genomics knowledge bases have developed rapidly, [1][2][3] higher-level phenomics knowledge bases (that is, comprehensive repositories for phenotype data that can be used on a genome-wide scale) are only now emerging 4 (for example, Mouse Phenome Database (www.jax.org/phenome) and Australian Phenomics Centre (www.apf.edu.au)). These informatics resources can advance molecular psychiatry research by helping researchers better define phenotype constructs, select specific phenotypic measures and ultimately develop multilevel models that specify both phene-phene and gene-phene associations.…”
Section: Introductionmentioning
confidence: 99%